Pembuatan Aluminium Berpori dengan metode Metalurgi Serbuk Berbahan Amonium Hidrogen Karbonat ((NH4)HCO3) sebagai Space Holder beserta Karakterisasinya - Aris Widyo Nugroho; Iswanto Iswanto (Universitas Muhammadiyah Yogyakarta, 2018)
The reseacrh on fabrication of porous aluminum using powder metallurgy technique with amonium hidrogen karbonat as space holder has been carried out. The space holder powder with various space holder mass fraction of 20%,30%, 40% and 50% in 5 gram of total mass and the aluminum powder were put into a can for mixing process. Afterward the mixed powder was compacted at 300 kg/cm2 to obtain the green body. Density of the green body was then determined by measuring its dimension and the mass. Following this, the green body was put in a furnace and heated up to 200oC with holding time of 60 minutes for space holder removal. The second heating up was carried out up to 650oC with holding time of 60 minutes for sintering process and the furnace was then switched off for cooling. Porosity of the sintered porous aluminum was calculated and its microstructure was examined using an optical microscop. The compressive strength of the porous material was evaluated using universal testing machine. The result show that the porosity increases with an increase of the mass fraction in the range of 56-74% with the compressive strength in opposite way. The strength was found in the range of 1.2-15.7 MPa. All specimens show a typical britlle materials.